OP0229 Correlation of the Integrated Cerebrospinal Fluid Interleukin-6 Level with Brainstem Atrophy in Chronic Progressive Neuro-BehÇEt's Disease. (10th June 2014) - Kikuchi, H.; Nogawa-Takayama, M.; Asako, K.; Okamoto, A.; Nanki, T.; Kono, H.; Hirohata, S.
Abstract : Background: Central nervous system (CNS) involvement is a serious complication of Behçet's disease and is referred to as neuro-Behçet's disease (NB). NB is classified into acute type (ANB) and chronic progressive type (CPNB), depending on the clinical characteristics. CPNB is characterized by intractable, slowly progressive neurobehavioral changes, ataxia and dysarthria, which lead to severe disability and deterioration (1). Recently, we have found that brainstem atrophy is significantly more prevalent in CPNB than in ANB or non-NB, indicating that brainstem atrophy is a frequent and specific finding in CPNB (2). Objectives: The goal of the study was to examine whether the integrated cerebrospinal fluid (CSF) interleukin-6 level in the first 6 months after diagnosis is correlated with brainstem atrophy by quantitative analysis of magnetic resonance imaging (MRI) scans. Methods: The subjects were 10 patients (9 males and 1 female; all HLA-B51 positive; age at first MRI: 35.1±11.6 years old [mean ± SD]) who had been diagnosed with CPNB. The integrated CSF IL-6 level was calculated from the area under the curve (AUC) in a kinetic analysis of CSF IL-6 from the time of diagnosis until 6 months after diagnosis. The areas of midbrain tegmentum and pons were measured on mid-sagittal sections of T1-weighted images using NIH Image J ver.1.45 software (ver.1.46, National Institutes of Health: NIH, U.S. [http://rsbweb.nih.gov/ij/index.html ]). Results: The kinetics analysis showed that brainstem atrophy progressed most markedly in the first 2 years after diagnosis of CPNB. As shown in the Figure, integrated CSF IL-6 (0-0.5 years) was significantly correlated with brainstem atrophy rate in the first 2 years (0-2 years). Conclusions: These results indicate that higher levels of CSF IL-6 in the first 6 months after diagnosis are strongly associated with greater progression of brainstem atrophy in CPNB. This suggests that an appropriate therapeutic intervention to reduce CSF IL-6 is required as early as possible upon diagnosis of CPNB. References: Hirohata S. et al., Behçet's disease. Arthritis Res Ther 2003; 5:139-46. Hirohata S. et al., Clinical characteristics of neuro-Behçet's disease in Japan: a multicenter retrospective analysis. Mod Rheumatol 2012; 22: 405-13. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1610